Highly thermally conductive graphene phase change thermal pad and method of making same

CN123025536APending Publication Date: 2026-11-03BEIJING MICROENTHALPY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611042009.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

[0006]本发明旨在提供一种具有高导热、高压缩回弹、无泄漏固-固相变储能功能的石墨烯泡沫导热垫片,并提供一套结构可控、工艺稳定、可规模化生产的制备方法,解决现有导热垫片在高功率密度电子设备热管理中“导热不足、回弹差、相变泄漏、热响应滞后”等核心问题

Benefits of technology

1、石墨烯理论导热率可达5300W/mk,本发明通过特定的发泡工艺、取向工艺以及真空浸渍工艺,使得石墨烯相变导热垫片的导热率可达130W/mk,同时热阻可降低至0.05℃•cm2/w以下,此外相变材料的加入,使得垫片的整体导热性能以及压缩回弹性能得到了进一步加强,同时也赋予了垫片的第二功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123025536A_ABST
    Figure CN123025536A_ABST
Patent Text Reader

Abstract

The application belongs to the field of heat-conducting interface materials, and particularly relates to a high-heat-conducting graphene phase-change heat-conducting gasket and a preparation method thereof. The preparation method comprises the following steps: foaming treatment is performed on a graphene film, a low-temperature pretreatment is performed in a program to remove foaming residues, a graphitization treatment is performed under light pressure, a phase-change material is immersed and vacuum heat flat pressing treatment is performed, a surface is coated with an adhesive and heat pressing solidification is performed after stacking, and the graphene phase-change heat-conducting gasket is obtained through longitudinal cutting, and optional polyimide film edge sealing treatment. The application provides a graphene foam heat-conducting gasket with high heat conduction, high compression resilience, no leakage, solid-solid phase-change energy storage function, and provides a preparation method with controllable structure, stable process and scalable production, and solves the core problems of the existing heat-conducting gasket, such as insufficient heat conduction, poor resilience, phase-change leakage and thermal response lag, in the thermal management of high-power density electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermally conductive interface materials, specifically relating to a high thermal conductivity graphene phase change thermally conductive pad and its preparation method. Background Technology

[0002] With the rapid development of electronic devices towards higher power density, miniaturization, and flexibility, the resulting transient high heat flux density poses unprecedented challenges to thermal management materials. Traditional thermal interface materials (TIMs), such as thermal pads, not only need to possess excellent longitudinal thermal conductivity to quickly dissipate heat, but also need to maintain stable interfacial contact and long-term reliability under conditions of installation tolerances and mechanical vibration.

[0003] Traditional filler-type thermal pads (e.g., CN119039643A, CN108504016A) typically use polymers such as silicone rubber and polyolefins as the matrix, and improve thermal conductivity by filling them with inorganic thermally conductive particles such as alumina, boron nitride, and silicon carbide. Their thermal conductivity is generally below 10 W / (m•K), making it difficult to meet the heat dissipation requirements of high-power devices. Graphene laminated thermal pads (e.g., CN212097805U, CN115092921A) use highly thermally conductive graphene films through stacking, adhesive bonding, or a W-shaped bending structure. Their structure is essentially a rigid layered or filled composite material, lacking a three-dimensional, interconnected elastic porous structure, resulting in poor compression resilience (typically below 40%). Phase change composite materials based on graphene foam (such as CN117887421A) use three-dimensional graphene foam as a carrier to composite phase change materials. The graphene foam skeleton is composed of "graphene foam + fiber + nanoparticles", which has a complex structure and has not been specifically optimized for thermal conductivity and elasticity. It is difficult to achieve a high thermal conductivity of over 100 W / (m•K) and a high compression resilience of over 70% at the same time. Furthermore, an effective interfacial heat conduction enhancement mechanism has not been established, which limits the full utilization of thermal conductivity.

[0004] Current technologies struggle to simultaneously achieve ultra-high thermal conductivity (>100 W / (m•K)), high elastic compressive resilience (>70%), and stable, leak-free phase change energy storage capabilities within the same material system. Existing preparation methods are mostly limited to the laboratory stage, with fragmented process steps or demanding conditions. A complete, coherent, and scalable process chain integrating "multi-stage heat treatment - controllable graphitization - vacuum pressure impregnation - flat pressing" has not yet been proposed and validated, hindering large-scale and commercial applications.

[0005] Against this backdrop, the development of next-generation thermal pads that integrate efficient heat conduction, mechanical buffering, and active heat storage / release functions has become an urgent need. Summary of the Invention

[0006] This invention aims to provide a graphene foam thermal pad with high thermal conductivity, high compression resilience, and leak-free solid-solid phase change energy storage function. It also provides a controllable, stable, and scalable manufacturing method to solve the core problems of existing thermal pads in the thermal management of high-power-density electronic devices, such as insufficient thermal conductivity, poor resilience, phase change leakage, and delayed thermal response. The thermal pad is suitable for thermal management scenarios of electronic devices (such as CPUs, GPUs, power modules, 5G communication equipment, and new energy vehicle battery packs), and is particularly suitable for high-end applications with stringent requirements for thermal response speed, long-term stability, leak-free operation, and energy buffering.

[0007] This invention first provides a method for preparing a high thermal conductivity graphene phase change thermal pad, comprising the following steps: (1) The graphene film is foamed to obtain a graphene foam sheet precursor. (2) The graphene foam sheet precursor and graphite paper are stacked in a cross-layer and placed in a forced-air drying oven for medium and low temperature pretreatment to remove foaming residue; (3) Apply light pressure to the upper and lower surfaces of the pretreated graphene foam precursor with a graphite plate and graphitize it at high temperature to obtain graphene foam. (4) Place the graphene foam sheet in a container and vacuum degas it. Then add the phase change solution to the container and pressurize it. After impregnation, remove the excess phase change solution from the surface, dry it and vacuum hot flat pressing. Coat the surface of the graphene phase change foam sheet with an adhesive, stack multiple layers and then hot press to cure it to obtain the graphene phase change foam block. (5) The graphene phase change foam block is longitudinally cut to obtain a graphene phase change thermal conductive pad.

[0008] In some embodiments, in step (4), the mass ratio of the phase change material to the solvent in the phase change solution is 1:7-1:45 (preferably 1:2-1:13); the phase change material is tris(hydroxymethyl)aminomethane (tris), and the solvent is selected from ethanol and / or deionized water. Tris(hydroxymethyl)aminomethane, as a phase change material with high latent heat of phase change, has solid-solid phase change characteristics, so that when it is filled into a porous framework material, there is no risk of leakage due to its phase change. At the same time, the introduction of graphene not only provides heterogeneous nucleation sites, but also acts as an epitaxial template to induce grain refinement, thereby reducing supercooling and exhibiting an elastomer state at room temperature. This characteristic further enhances the high compressive resilience of the thermal pad under low stress, and at the same time, it gives the graphene thermal pad another function: storing thermal energy.

[0009] In some implementations, in step (4), the amount of adhesive used is 0.2-3 g / cm³. 2 (Preferred concentration: 0.3-1.5 g / cm³) 2The adhesive is selected from one or more of silicone resin, polyurethane, flexible epoxy resin, and modified silicone resin. The hot-press curing pressure is 0.1 MPa and the temperature is 65℃.

[0010] In some implementations, in step (4), the density of the graphene foam sheet is 0.1-0.5 g / cm³. 3 (Preferred concentration: 0.25-0.35 g / cm³) 3 Thickness 300-2000μm (preferably 350-500μm).

[0011] In some implementations, step (4) involves the following steps: The graphene foam sheet is placed in a vacuum chamber with a vacuum level of 0.01-0.1 MPa and vented for 10-60 minutes to provide an internal and external pressure difference for the subsequent introduction of the phase change material. The pressure impregnation process involves introducing inert gas to raise the pressure of the vacuum chamber to 0.5-3 MPa (preferably 1-2 MPa) and impregnating for 10-60 minutes. The vacuum hot pressing process uses a pressure of 500-1000 kg, a vacuum level of 0.21 MPa, and a temperature of 55-150 °C. The vacuum hot pressing process ensures surface flatness and, through the action of thermal pressure, bridges the phase change material with the framework material, reducing the interfacial thermal resistance and improving overall thermal conductivity.

[0012] In some implementations, in step (1), the graphene film is selected from graphene oxide film, mechanically exfoliated graphene film, reduced graphene oxide film or CVD-grown graphene film; the foaming treatment is as follows: the foaming agent and the foaming inducer are mixed and placed together with the graphene film in a foaming box for 5-15s (preferably 3-5s), and then dried after being taken out.

[0013] In some embodiments, in step (1), the foaming agent is selected from one or more of hydrazine hydrate, ascorbic acid-α, hydroiodic acid, and ammonium bicarbonate; the foaming inducing agent is selected from one or more of deionized water, ethanol, and glycerol; and the density of the graphene film is 0.2-0.75 g / cm³. 3 (Preferred concentration: 0.2-0.35 g / cm³) 3 The mass ratio of foaming agent to foaming inducer is 1:0.02~0.08 (preferably 1:0.027~0.056). The mass ratio of graphene film to foaming agent is 2~4:1.

[0014] In some implementations, step (2) involves a medium-low temperature pretreatment: the material is placed in a forced-air drying oven for programmed temperature increase (e.g., 25-65℃ for 9 hours, 65-75℃ for 6 hours, 75-90℃ for 2 hours, 90-120℃ for 1 hour, and 120-250℃ for 0.5 hours). This step aims to thoroughly and gently remove moisture and foaming agent residue from the precursor, preventing them from violently evaporating and damaging the already formed fine porous structure during subsequent high-temperature treatment. Simultaneously, the cross-stacking of graphite paper provides mechanical support and thermal stress homogenization to the film during the drying process. The ultra-high thermal conductivity of the graphite paper helps alleviate thermal stress caused by mismatched coefficients of thermal expansion and temperature gradients, preventing the graphene foam sheet from twisting and collapsing due to uneven stress during multi-stage heating.

[0015] In some implementations, step (3) involves graphitization as follows: the pretreated precursor is placed in a graphitization furnace, and light pressure is applied to its upper and lower surfaces using graphite plates (total weight 3-9 kg, preferably 4-6 kg). Under an inert protective atmosphere, the temperature is increased to 2800 °C at a rate of 10-15 °C / min and held for 2 hours. This process achieves deep graphitization of graphene oxide, repairs lattice defects, and greatly improves the intrinsic thermal conductivity of the framework. Simultaneously, under pressure assistance, a graphene foam framework with high crystallinity, high connectivity, and excellent elasticity is formed, with a density of 0.1-0.5 g / cm³ and a thickness of 300-2000 μm.

[0016] In some implementations, in step (5), the cutting equipment is one of laser cutting, wire cutting, or knife cutting (preferably wire cutting), the cutting speed is 0.1-100 mm / min (preferably 0.5-1.8 mm / min), and the cutting angle is 0-180° (preferably 50-75°). When cutting at a cutting angle of 50-70°, the gasket forms an oblique compression wave during compression, resulting in a more uniform stress distribution and a 30% increase in the final product's resilience.

[0017] In some embodiments, the preparation method further includes step (6): sealing the graphene phase change thermally conductive pad, preferably with a polyimide film. Sealing ensures the insulation performance of the graphene phase change thermally conductive pad to meet the requirements of actual operating conditions.

[0018] The present invention also provides a high thermal conductivity graphene phase change thermal pad prepared by the above preparation method.

[0019] Compared with the prior art, the beneficial effects of the present invention include at least the following: 1. Graphene has a theoretical thermal conductivity of up to 5300 W / mK. This invention, through specific foaming, orientation, and vacuum impregnation processes, enables the thermal conductivity of graphene phase change thermal pads to reach 130 W / mK, while simultaneously reducing thermal resistance to 0.05 °C•cm. 2 Below / w, the addition of phase change material further enhances the overall thermal conductivity and compression resilience of the gasket, while also giving the gasket a secondary function.

[0020] 2. The tris(hydroxymethyl)aminomethane used in this invention is a solid-solid phase change material that will not flow out under pressure when the phase change occurs. As a phase change reinforcing material in the graphene phase change thermal pad, it avoids material loss or performance degradation during long-term use and greatly improves its thermal stability.

[0021] 3. The high thermal conductivity graphene phase change thermal pad of the present invention adopts an integrated structure of graphene foam and solid-solid phase change material. The phase change material is combined with the three-dimensional interconnected graphene foam network to form a continuous and stable integrated "skeleton-functional phase" composite. It has synergistic characteristics of high thermal conductivity, high compressibility and excellent resilience, and has significantly reduced interfacial thermal resistance. Moreover, the preparation method can be mass-produced. Attached Figure Description

[0022] Figure 1 To prepare the microstructure of the graphene foam sheet of Example 1. Detailed Implementation

[0023] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Examples of the embodiments are shown in the accompanying drawings. It should be understood that the specific embodiments described in the following embodiments of the invention are merely illustrative examples of specific implementations of the invention and are intended to explain the invention, but do not constitute a limitation thereof.

[0024] The endpoints of the ranges and any values ​​disclosed herein are not limited to the exact ranges or values, which should be understood to include those close to them.

[0025] Example 1: Preparation method of graphene phase change thermal pad The preparation examples 1-10 of the present invention were prepared using the following method, with specific parameters as shown in Example 2.

[0026] Step (1): Preparation of graphene foam precursor The material uses graphene oxide film as raw material, and one or more of hydrazine hydrate, ascorbic acid-α, hydroiodic acid, and ammonium bicarbonate as foaming agents, and one or more of deionized water, ethanol, and glycerol as foaming inducing agents. The density of graphene oxide films is 0.2-0.75 g / cm³. 3 The mass ratio of foaming agent to foaming inducer is 1:0.02~0.08; The foaming agent and foaming inducer are mixed and placed together with the graphene oxide film in a foaming chamber for 5-15 seconds. After being removed, the mixture is dried in a forced-air drying oven at 65°C to obtain the graphene foam sheet precursor.

[0027] Step (2): Low-temperature pretreatment The precursor obtained in step 1 was cross-stacked with graphite paper and placed in a forced-air drying oven for programmed temperature treatment (25-65℃ for 9 hours, 65-75℃ for 6 hours, 75-90℃ for 2 hours, 90-120℃ for 1 hour, and 120-250℃ for 0.5 hours). This step aims to thoroughly and gently remove moisture and residual foaming agent from the precursor, preventing them from violently evaporating and damaging the already formed fine porous structure during subsequent high-temperature treatment. Simultaneously, the cross-stacked graphite paper provides mechanical support and homogenizes thermal stress during the drying process, preventing the graphene foam sheet from twisting and collapsing due to uneven stress during multiple temperature stages.

[0028] Step (3): Graphitization treatment The pretreated precursor is placed in a graphitization furnace, and light pressure is applied to its upper and lower surfaces using graphite plates (total weight 3-9 kg, preferably 4-6 kg). Under an inert protective atmosphere (argon), the temperature is increased to 2800℃ at a rate of 10-15℃ / min and held for 2 hours. This process achieves deep graphitization of graphene oxide, repairs lattice defects, and significantly improves the intrinsic thermal conductivity of the framework. Simultaneously, under pressure assistance, a graphene foam framework with high crystallinity, high connectivity, and excellent elasticity is formed, with a density of 0.1-0.5 g / cm³ and a thickness of 300-2000 μm. In a specific preparation example, the microstructure of the graphene foam sheet is as follows: Figure 1 As shown (Preparation Example 1).

[0029] Step (4): Preparation of graphene phase change foam blocks The graphene foam sheet obtained in step 4 is used as the frame material, tris(hydroxymethyl)aminomethane (tris) is used as the phase change material, ethanol and deionized water are used as solvents, and one or more of the following are used as binders: silicone resin, polyurethane, flexible epoxy resin, and modified silicone resin. The density of graphene foam sheets is 0.1-0.5 g / cm³. 3 Thickness 500-120μm; mass ratio of phase change material to solvent 1:7-1:45; binder dosage 0.2-3g / cm³ 2 ; The graphene foam sheet was placed in a vacuum chamber with a vacuum degree of 0.1 MPa for 30 minutes to allow for venting, providing an internal and external pressure difference for the subsequent introduction of the phase change material. Then, the prepared phase change solution was placed in the chamber, and an inert gas was introduced into the vacuum chamber to raise the pressure to 0.5-3 MPa. After immersion for 15 minutes, the sheet was removed and placed in a cleaning solution to remove excess phase change solution from the surface. The cleaned sheet was then placed in a vacuum drying oven to dry, removing the cleaning solution and solvent. Finally, the dried phase change foam sheet was subjected to vacuum hot flattening treatment (preferably at a pressure of 500-1000 kg, a vacuum degree of 0.21 MPa, and a temperature of 55-150℃). This process ensured the surface flatness and, through the effect of thermal pressure, created a bridge between the phase change material and the framework material, reducing the interfacial thermal resistance and improving the overall thermal conductivity. Tris(hydroxymethyl)aminomethane, as a phase change material with high latent heat of phase change, does not pose a risk of leakage when filled into a porous framework material due to its solid-solid phase change characteristics. At the same time, the introduction of graphene not only provides heterogeneous nucleation sites but also acts as an epitaxial template to induce grain refinement, thereby lowering the phase change temperature (a decrease of 26.8℃ from 62.5℃). It exhibits an elastomer state at room temperature, which further enhances the high compressive resilience of the thermal pad under low stress and also endows the graphene thermal pad with another function: storing thermal energy.

[0030] Then, the surface of the graphene phase change foam sheet is coated with adhesive using a dispensing machine, and the sheets are stacked one layer of foam sheet and one layer of adhesive. After stacking to the target height, the sheets are placed under a hot press and subjected to a certain pressure (0.1MPa) and temperature (65℃) to cure and bond them into a whole, thus obtaining the graphene phase change foam block.

[0031] Step (5): Preparation of graphene phase change thermal pad The foam block obtained in step (4) is placed on a cutting device for longitudinal cutting to obtain a graphene phase change thermal conductive pad. The cutting device is one of laser cutting, wire cutting, or knife cutting, with a cutting speed of 0.1-100 mm / min and a cutting angle of 0-180° (preferably 50-75°). When cutting at a cutting angle of 50-70°, the pad forms an oblique compression wave during compression, resulting in a more uniform stress distribution and a 30% increase in the final product's resilience.

[0032] Step (6): Packaging Process To ensure the insulation performance of graphene phase change thermal conductive pads, edge sealing is required to meet the needs of actual operating conditions. This is achieved by sealing the four sides with a polyimide film using an edge-wrapping technique.

[0033] Example 2: Preparation parameters of preparation examples 1-10 (1) Preparation process parameters for Example 1 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.08, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:8, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.1 g / cm³. 3 The thickness is 500μm; The adhesive is silicone, and the amount of adhesive used is 0.8 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0034] (2) The preparation process parameters for Example 2 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.04, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:8, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.15 g / cm³. 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 0.8 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0035] (3) The preparation process parameters for Example 3 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.04, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 10-15℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 5kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:8, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.2 g / cm³. 3 The thickness is 200μm; The adhesive is silicone, and the amount of adhesive used is 0.8 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0036] (4) The preparation process parameters for Example 4 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature is increased to 2800℃ at a rate of 10-15℃ / min and held for 2 hours to perform graphitization treatment. The process is carried out with a load of 10kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:8, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.5 g / cm³. 3 The thickness is 120μm; The adhesive is silicone, and the amount of adhesive used is 0.8 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0037] (5) The preparation process parameters for Example 5 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:5, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.15 g / cm³. 3 The thickness is 350μm; Adhesive type: silicone; Adhesive dosage: 1.5 g / cm³ 2Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0038] (6) The preparation process parameters for Example 6 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming inducer is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 1:3, the mass ratio of foaming agent to foaming inducer is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:5, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.15 g / cm³. 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 2g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0039] (7) The preparation process parameters for Example 7 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming inducer is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 1:3, the mass ratio of foaming agent to foaming inducer is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:5, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.15 g / cm³. 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 0.3 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 55°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0040] (8) The preparation process parameters for Example 8 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming inducer is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 1:3, the mass ratio of foaming agent to foaming inducer is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent was a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent was 1:5, the impregnation pressure was 5 MPa, the impregnation time was 15 min, the vacuum hot pressing pressure was 650 kg, the vacuum degree was 0.21 MPa, the temperature was 75℃, and the graphene foam sheet had a density of 0.15 g / cm³. 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 0.3 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 65°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0041] (9) The preparation process parameters for Example 9 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent is a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent is 1:5, the impregnation pressure is 5 MPa, the impregnation time is 15 min, the vacuum hot flat pressure is 650 kg, the vacuum degree is 0.21 MPa, and the temperature is 75℃. Graphene foam sheet with a density of 0.15 g / cm³ 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 0.3 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 1.5 mm / min; Cutting angle: 70°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0042] (10) The preparation process parameters for Example 10 are as follows: The density of the graphene oxide film is 0.9 g / cm³. 3 The foaming agent is hydrazine hydrate, the foaming induction agent is a 2:1 mixture of deionized water and ethanol, the mass ratio of graphene oxide film to foaming agent is 3:1, the mass ratio of foaming agent to foaming induction agent is 1:0.040, the foaming time is 5s, and the drying temperature is 65℃. The foaming process was pretreated using a temperature regime curve of 45℃ for 9 hours, 65℃ for 6 hours, 75℃ for 2 hours, 135℃ for 1 hour, and 250℃ for 0.5 hours. Under the protection of argon, the temperature was increased to 2800℃ at a rate of 13℃ / min and held for 2 hours to perform graphitization treatment. The process was carried out with a load of 4kg. The solvent is a 5% ethanol aqueous solution, the mass ratio of phase change material to solvent is 1:2, the impregnation pressure is 5MPa, the impregnation time is 15min, the vacuum hot flat pressure is 650kg, the vacuum degree is 0.21MPa, and the temperature is 75℃. Graphene foam sheet with a density of 0.3 g / cm³ 3 The thickness is 350μm; The adhesive is silicone, and the amount of adhesive used is 0.3 g / cm³. 2 Curing time: 4 hours; Curing pressure: 0.1 MPa. Cutting speed: 0.5 mm / min; Cutting angle: 70°. Polyimide is used for edge sealing, with an edge sealing distance of 0.05mm.

[0043] Example 3: Experimental Control Comparative Example 1: The preparation process in this example is basically the same as that in Example 10, except that the phase change material was not impregnated in the graphene foam sheet.

[0044] Comparative Example 2: A commercially available graphene phase change (paraffin) thermal pad.

[0045] Example 4: Performance testing of preparation examples 1-10 and comparative examples 1-2 The performance test results of the samples are shown in Table 1. Compared with Comparative Example 1, which is without impregnated phase change material, the thermal resistance of Preparation Examples 1-10 is significantly reduced (especially at 40 psi), and the resilience is significantly improved. Compared with commercially available gaskets, the thermal conductivity is significantly improved, and the resilience is significantly improved.

[0046]

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and do not constitute a limitation on the content of the present invention. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including combining various technical features in any other suitable manner. These simple modifications and combinations should also be regarded as the content disclosed in the present invention and all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity graphene phase change thermal pad, characterized in that, Includes the following steps: (1) The graphene film is foamed to obtain a graphene foam sheet precursor. (2) The graphene foam sheet precursor and graphite paper are stacked in a cross-layer and placed in a forced-air drying oven for medium and low temperature pretreatment to remove foaming residue; (3) Apply light pressure to the upper and lower surfaces of the pretreated graphene foam precursor with a graphite plate and graphitize it at high temperature to obtain graphene foam. (4) Place the graphene foam sheet in a container and vacuum degas it. Then add the phase change solution to the container and pressurize it. After impregnation, remove the excess phase change solution from the surface, dry it and vacuum hot flat pressing. Coat the surface of the graphene phase change foam sheet with an adhesive, stack multiple layers and then hot press to cure it to obtain the graphene phase change foam block. (5) The graphene phase change foam block is longitudinally cut to obtain a graphene phase change thermal conductive pad.

2. The preparation method according to claim 1, characterized in that, In step (4), the mass ratio of phase change material to solvent in the phase change solution is 1:7-1:45 (preferably 1:2-1:13); the phase change material is tris(hydroxymethyl)aminomethane (tris), and the solvent is selected from ethanol and / or deionized water; The amount of adhesive used is 0.2-3 g / cm³. 2 (Preferred concentration: 0.3-1.5 g / cm³) 2 The adhesive is selected from one or more of silicone resin, polyurethane, flexible epoxy resin, and modified silicone resin. The pressure for hot pressing curing is 0.1 MPa, and the temperature is 65℃.

3. The preparation method according to claim 1, characterized in that, In step (4), the density of the graphene foam sheet is 0.1-0.5 g / cm³. 3 (Preferred concentration: 0.25-0.35 g / cm³) 3 Thickness 300-2000μm (preferably 350-500μm).

4. The preparation method according to claim 1, characterized in that, In step (4), the vacuum exhaust process is as follows: the graphene foam sheet is placed in a vacuum chamber with a vacuum degree of 0.01-0.1MPa and the exhaust process is carried out for 10-60 minutes. The pressure impregnation process is as follows: inert gas is introduced to increase the pressure of the vacuum tank to 0.5-3MPa (preferably 1-2MPa), and impregnation is carried out for 10-60 minutes; The vacuum heat flattening treatment has a pressure of 500-1000 kg, a vacuum degree of 0.21 MPa, and a temperature of 55-150℃.

5. The preparation method according to claim 1, characterized in that, In step (1), the graphene film is selected from graphene oxide film, mechanically exfoliated graphene film, reduced graphene oxide film or CVD-grown graphene film. The foaming process involves mixing the foaming agent and the foaming inducer, then placing them together with the graphene film in a foaming chamber for 5-15 seconds (preferably 3-5 seconds), followed by drying.

6. The preparation method according to claim 1, characterized in that, In step (1), the foaming agent is selected from one or more of hydrazine hydrate, ascorbic acid-α, hydroiodic acid, and ammonium bicarbonate; the foaming inducing agent is selected from one or more of deionized water, ethanol, and glycerol; the density of the graphene film is 0.2-0.75 g / cm³. 3 (Preferred concentration: 0.2-0.35 g / cm³) 3 The mass ratio of foaming agent to foaming inducer is 1:0.02~0.08 (preferably 1:0.027~0.056); the mass ratio of graphene film to foaming agent is 2~4:

1.

7. The preparation method according to claim 1, characterized in that, In step (2), the low-temperature pretreatment is as follows: the temperature is increased by a program in a forced-air drying oven, and the temperature is maintained at 25-65℃ for 9 hours, 65-75℃ for 6 hours, 75-90℃ for 2 hours, 90-120℃ for 1 hour, and 120-250℃ for 0.5 hours.

8. The preparation method according to claim 1, characterized in that, In step (3), the graphitization process is as follows: the pretreated precursor is placed in a graphitization furnace, and light pressure is applied to its upper and lower surfaces with graphite plates (total weight 3-9 kg, preferably 4-6 kg); under an inert protective atmosphere, the temperature is raised to 2800℃ at a rate of 10-15℃ / min and held for 2 hours.

9. The preparation method according to claim 1, characterized in that, In step (5), the cutting equipment is one of laser cutting, wire cutting, and knife cutting (preferably wire cutting), the cutting speed is 0.1-100mm / min (preferably 0.5-1.8mm / min), and the cutting angle is 0-180° (preferably 50-75°). The preparation method further includes step (6): sealing the graphene phase change thermal pad, preferably with a polyimide film.

10. A high thermal conductivity graphene phase change thermal pad prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Thermal conduction gasket and preparation method thereof

    CN108504016A

  • Graphene heat-conducting gasket and preparation method thereof

    CN115092921A

  • Ultrahigh-thermal-conductivity graphene foam energy storage material and preparation method thereof

    CN117887421A

  • Phase-change material super-soft high-thermal-conductivity composite material gasket and preparation method thereof

    CN119039643A

  • Graphene heat-conducting gasket with sandwich structure

    CN212097805U